Analisis faktor penentu keberhasilan implementasi sistem informasi akademik pada ISB Atma Luhur - Amri, Amri; Isnanto, R Burham; Alkodri, Ari Amir; Bakti Atmaja, R Ferry (Journal of Business & Banking, 2024)
To support higher education, academic information systems are required. However, user satisfaction, especially among students, is crucial to the system’s success. The aim of this research was to investigate the relationship between student happiness and the quality of academic information systems at the Atma Luhur Institute of Science and Business (ISB), using ease of use as a mediating variable. This study aims to analyze the factors influencing student satisfaction with the academic information system at ISB Atma Luhur. Using structural equation modeling (SEM) with a partial least squares (PLS) approach, this research examines the impact of information quality, system quality, and service quality on ease of use and student satisfaction. Data were collected through questionnaires distributed to 200 students who use the information system. The results indicate that information quality and system quality significantly affect ease of use, which in turn affects student satisfaction. Additionally, service quality has a direct and significant impact on student satisfaction. These findings contribute significantly to the development of academic information systems by highlighting aspects that need attention to enhance user satisfaction. The practical implications of this research include recommendations for improving information quality, system quality, and service quality within the context of academic information systems.